Cell-based versus corticosteroid injections for knee pain in osteoarthritis: a randomized phase 3 trial - Mautner, Ken; Gottschalk, Michael; Boden, Scott D.; Akard, Alison; Bae, Won C.; Black, Lora; Boggess, Blake; Chatterjee, Paramita; Chung, Christine B.; Easley, Kirk A.; Gibson, Greg; Hackel, Josh; et al. (Nature medicine, 2023)
Various types of cellular injection have become a popular and costly treatment option for patients with knee osteoarthritis despite a paucity of literature establishing relative efficacy to each other or corticosteroid injections. Here we aimed to identify the safety and efficacy of cell injections from autologous bone marrow aspirate concentrate, autologous adipose stromal vascular fraction and allogeneic human umbilical cord tissue-derived mesenchymal stromal cells, in comparison to corticosteroid injection (CSI). The study was a phase 2/3, four-arm parallel, multicenter, single-blind, randomized, controlled clinical trial with 480 patients with a diagnosis of knee osteoarthritis (Kellgren–Lawrence II–IV). Participants were randomized to the three different arms with a 3:1 distribution. Arm 1: autologous bone marrow aspirate concentrate ( n = 120), CSI ( n = 40); arm 2: umbilical cord tissue-derived mesenchymal stromal cells ( n = 120), CSI ( n = 40); arm 3: stromal vascular fraction ( n = 120), CSI ( n = 40). The co-primary endpoints were the visual analog scale pain score and Knee injury and Osteoarthritis Outcome Score pain score at 12 months versus baseline. Analyses of our primary endpoints, with 440 patients, revealed that at 1 year post injection, none of the three orthobiologic injections was superior to another, or to the CSI control. In addition, none of the four groups showed a significant change in magnetic resonance imaging osteoarthritis score compared to baseline. No procedure-related serious adverse events were reported during the study period. In summary, this study shows that at 1 year post injection, there was no superior orthobiologic as compared to CSI for knee osteoarthritis. ClinicalTrials.gov Identifier: NCT03818737 The multicenter phase 3 trial of stem cell therapy for osteoarthritis (MILES) for knee pain revealed that cell therapies showed no significant difference in knee pain outcomes, compared to corticosteroid injections, 1 year following treatment.